2022
DOI: 10.1002/wnan.1820
|View full text |Cite
|
Sign up to set email alerts
|

Application of vinyl polymer‐based materials as nucleic acids carriers in cancer therapy

Abstract: Nucleic acid‐based therapies have changed the paradigm of cancer treatment, where conventional treatment modalities still have several limitations in terms of efficacy and severe side effects. However, these biomolecules have a short half‐life in vivo, requiring multiple administrations, resulting in severe suffering, discomfort, and poor patient compliance. In the early days of (nano)biotechnology, these problems caused concern in the medical community, but recently it has been recognized that these challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 186 publications
0
1
0
Order By: Relevance
“…These results are consistent with several other studies that have shown that the composition, architecture, and concentration of copolymers have a major impact on their toxicity. 41,42 In vitro hydrolytic degradation of the star-shaped BCPs…”
Section: In Vitro Cytotoxicity Of Amphiphilic Bcpsmentioning
confidence: 99%
“…These results are consistent with several other studies that have shown that the composition, architecture, and concentration of copolymers have a major impact on their toxicity. 41,42 In vitro hydrolytic degradation of the star-shaped BCPs…”
Section: In Vitro Cytotoxicity Of Amphiphilic Bcpsmentioning
confidence: 99%